Uma ferramenta para criação de clusters virtuais para execução de aplicações paralelas e distribuídas em nuvens públicas - Silva, Antônio Carlos (2020)
Cloud computing is a technology that allows the distribution of its computing services, providing computational resources, through the deployment models for a computing cloud, the services offered by clouds are part of the base infrastructure of the Internet, becoming a competitive differential for use in distributed applications. With this in mind, the present work has the objective of developing a tool that allows selecting between two or more options of public clouds for the creation of a virtual cluster focused on the programming of parallel and distributed applications, acting at the IaaS level of a public cloud. To validate the functionalities of the tool, a programming exercise was carried out in the created cluster, after the exercise was carried out, the questionnaire was applied to students and alumni, in order to carry out a qualitative assessment of the proposed tool in order to obtain results from regarding the usability of the tool. With the consolidated results, we carried out the treatment of the data obtained in the evaluation. We concluded with this work, that the developed tool is capable of creating virtual clusters on public cloud platforms approached through the IaaS service model, in which the user makes use of virtual infrastructures for parallel and distributed programming practices.